Urogenital and Rectal Multisystem Organ Injury After Detonation of an Explosive Substance in the Rectum of a Schizophrenic Man - Zumrutbas, Ali E.; Baser, Aykut; Acar, Cenk I.; Ozlulerden, Yusuf; Okutan, Aysegul; Sahin, Umit Y.; Aybek, Zafer (ELSEVIER SCIENCE INC, 2014)
Penetrating injuries are caused by the injury of perineal area with gun or stab wounds, which may cause complex injuries or multiple organ injuries. Infections, bleeding, necrotizing fasciitis, ureterocutaneous fistulas, diverticulum, abscesses, narrowing, and incontinence may arise after urethral injuries. Although there are several case reports of urogenital system traumas in the literature, this case reports a schizophrenic patient who had a multisystem genitourinary and rectal trauma after self-detonation of an explosive in the rectum and managed with reconstructive surgery without any postoperative complications. Lower urinary tract anatomy was preserved and full continence was achieved after the surgical procedure. (C) 2014 The Authors. Published by Elsevier Inc. All rights reserved.
Keywords: Genitourinary trauma; Rectal trauma; Bladder; Urethral reconstruction